2014
DOI: 10.1002/phar.1435
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Discontinuations Due to Adverse Events in Patients Treated with Ceftaroline

Abstract: When given for off-label indications to 12 patients at our institutions, ceftaroline was associated with an unexpectedly high rate (75%) of discontinuation due to perceived adverse events, including hematologic toxicities and rash.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…9,25,26 Indeed, in the one report that included patients similar to ours (i.e., comorbid patients, long duration of therapy, off-label indications), among 12 inpatients treated with ceftaroline, 9 patients (75%) discontinued ceftaroline because of an ADR. 22 Reported ADRs similarly included cutaneous and hematologic findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,25,26 Indeed, in the one report that included patients similar to ours (i.e., comorbid patients, long duration of therapy, off-label indications), among 12 inpatients treated with ceftaroline, 9 patients (75%) discontinued ceftaroline because of an ADR. 22 Reported ADRs similarly included cutaneous and hematologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, some reports suggest that ceftaroline may be associated with more ADRs than identified in premarketing studies. 1622 Previously reported ceftaroline ADRs include neutropenia, thrombocytopenia, anemia, rashes, eosinophilic pneumonia, and AIN. 1619,21,22 We aimed to retrospectively describe ceftaroline’s pattern of use and resultant ADRs and HSRs in two large academic hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Sık görülen yan etkisi C. difficile ile ilişkili ishaldir. Hematolojik toksisite ve kızarıklıklar çok sayıda hastada görülmüştür (25) . Son dönemde yapılan bir çalışmada, seftobiprol'ün toplum kökenli pnömoni tedavisinde seftriakson ve linezolid kadar etkili olduğu gösterilmiştir (26) .…”
Section: Iic Sefalosporinlerunclassified
“…However, adverse effects related to ceftaroline use are rarely described. Multiple observational and case report studies have suggested that ceftaroline exposure is associated with higher rates of neutropenia than seemingly listed in the product package insert . The prolonged use of ceftaroline in off‐label, difficult‐to‐treat clinical scenarios may potentiate the risk of neutropenia and contribute to additional patient morbidity and mortality, particularly if adequate follow‐up laboratory monitoring is not performed …”
mentioning
confidence: 99%
“…Prolonged durations of high‐dose ceftaroline (i.e., 600 mg 3times daily) are typically prescribed for serious infections such as endocarditis or osteomyelitis . Although neutropenia is a known adverse effect of β‐lactam antibiotics, the number of reports suggesting ceftaroline‐associated neutropenia is concerning . Whereas the causal relationship of this association remains unclear when comparing ceftaroline to other β‐lactams, the potential effects of non–chemotherapy‐associated neutropenia could lead to an increased propensity for severe infection, hospital readmission, prolonged hospitalization length of stay (LOS), increased cost, and increased patient mortality …”
mentioning
confidence: 99%